Electrochemical Behavior and Direct Quantitative Determination of Paclitaxel - Jiaqi Lang (Frontiers in Chemistry, 2022)
The electrochemical behavior and direct quantitative determination of paclitaxel, a poorly soluble drug made into microemulsion, were researched by cyclic voltammetry in acetate buffer solutions (pH = 4.0) at a glassy carbon electrode. The results show that the oxidation process is irreversible and controlled by diffusion. Moreover, the effects of anodic peak current (Ipa), anodic peak potential, scan rate, pH, and the electrochemical redox mechanism have been studied. The anodic peak current varied linearly with paclitaxel concentration in the range of 5 × 10−5 mol/L to 5 × 10−4 mol/L, and the detection limit was 9.15 × 10−8 mol/L. The results of RSD (0.90%) and recovery (99.22%–101.69%) were obtained. Additionally, it has been proved that one electron and one proton are involved in the electrochemical redox process. The present research has been successfully used to determine paclitaxel in pure and real samples, which further supported the electrochemical behavior investigation of paclitaxel and direct determination of micro-emulsion.